2008
DOI: 10.1016/j.pain.2007.10.023
|View full text |Cite
|
Sign up to set email alerts
|

Increased pain sensitivity is not a risk factor but a consequence of frequent headache: A population-based follow-up study

Abstract: Altered pain sensitivity is believed to play an important role for chronification of headache. It has however mainly been evaluated in highly selected patients from headache clinics and never in longitudinal studies. The present study is a 12-year follow-up of a population-based study of primary headache disorders and pain perception, combining a diagnostic headache interview with examination of muscle tenderness and measurement of pressure pain thresholds in 1000 subjects drawn randomly from the general popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
75
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(81 citation statements)
references
References 32 publications
6
75
0
Order By: Relevance
“…The current data, however, do not demonstrate an increased risk of future LBP in the group of 'none-orremitted LBP' participants with the lowest PPTs. Thus, the current data suggest that the natural variability in constitutional pain sensitivity does not pose a distinct and separate risk factor for future LBP in itself, which corroborates the findings by Buchgreitz et al [3] on headache sufferers.…”
Section: Lbp Status and Hyperalgesiasupporting
confidence: 91%
See 1 more Smart Citation
“…The current data, however, do not demonstrate an increased risk of future LBP in the group of 'none-orremitted LBP' participants with the lowest PPTs. Thus, the current data suggest that the natural variability in constitutional pain sensitivity does not pose a distinct and separate risk factor for future LBP in itself, which corroborates the findings by Buchgreitz et al [3] on headache sufferers.…”
Section: Lbp Status and Hyperalgesiasupporting
confidence: 91%
“…This question has only been addressed to a lesser extent: The cohort study by Buchgreitz et al [3] examined the changes in cranial muscle pressure pain thresholds (PPTs) over a 12-year period and found that increased pain sensitivity correlated with development of chronic tension type headache. Thus, the authors concluded that increased pain sensitivity of cranial muscles develops as a consequence of chronic headache.…”
Section: Introductionmentioning
confidence: 99%
“…The psychophysical results disprove the central sensitization hypothesis, with the authors stating, "Premorbid PPT [pressure pain thresholds] poorly predict TMD incidence" (Slade et al 2014). Similar negative results are now also reported for development of chronic tension-type headache (Buchgreitz et al 2008), for low back pain (O'Neill et al 2011), and for development of widespread pain (Gupta et al 2007). Thus, there is a large contrast in predictability of chronic pain by brain parameters from that of peripheral sensitivity.…”
Section: The Corticolimbic System As a Predictor And Determinant Of Cmentioning
confidence: 61%
“…A number of studies in adults have demonstrated a strong association between headache, cervical and thoracic spine dysfunction (5) and an increased tenderness Table 3. Self-reported painful movements in adolescents without headache, with headache and stratified for type of headache to palpation of pericranial myofascial tissues (25). These studies suggest that increased tenderness is not only observed in TTH (15,16) but also in migraine (6).…”
Section: Discussionmentioning
confidence: 76%